RELIGIOUS RADICALISM FRAME IN THE ONLINE MEDIA NEWS (Framing Analysis Reporting Of â€œISISâ€ In Republika.co.id and Tempo.co) - Zamroni, Mohammad; Astuti, Yanti Dwi (Islam Futura, 2021)
This study aims to explore how the framing of Islamic radicalism through the reporting of the group "ISIS" in two online media, namely in Republika.com and Tempo.co with an impartiality perspective. The research method used is descriptive qualitative by using a discourse strategy that sees the text and its context as information that contributes to communicating the contents of the message. Primary and secondary data are obtained from news curators, online portals, and library studies. While the unit of analysis is ISIS radicalism news in Republika.co.id and Tempo.co in the period of August to December 2014 that falls within the three criteria of radicalism news, namely acts of violence, beliefs championed, old-fashioned views or rigid thoughts that underlie acts of violence using techniques framing analysis of Gamson and Modigliani models. The results showed that news about radical "ISIS" included in the category of news construction that was emotional, sadistic, provocative and without confirmation. In addition, the quality of reporting often adorns with words that appear hyperbole and bombastic, the coverage is less profound and changes in a matter of minutes. The trend of Tempo.co and Republika.co.id dramatizes and exaggerates what happens in conflict areas by using connoted language rather than language that has a literal meaning. Then it has not fulfilled the principle of impartiality of news which can be seen from the neutrality and balance of news that determines the quality of reporting.